Direct regeneration and characterization of plant derived from leaf in vitro culture Patchouli ( Pogostemon cablin, Benth) - Pappusamy, Arokiaraj; Fitriana, Sita; Salihon, Jailani; Amalina, Ida (2010)
Patchouli has huge potential to serve the pharmaceutical industries due to its fragrance and aromatic essential oils. To serve the needs of the pharmaceutical and perfume industries, there is an urgent need to mass propagate clonal copies of the desired patchouli plantlets. In order to generate genetically identical clonal copies of the desired cultivar, direct regeneration of patchouli plantlets by tissue culture using leaf explants was successful. The tissue culture formulation for direct regeneration employed Murashige and Skoog medium with 0,5 mg/l 2,4 D (2,4Dichlorofenoksiacetat) in combination with (0, 0.25, 0.5, 0.75, 1 mg/l) BAP (Benzyl Aminopurine). The best response for direct shoot regeneration was observed after 35 days occurred in media containing 0.75 mg/l of BAP without 2,4 D and this gave the highest efficiency of regeneration frequency of leaf (88%) and highest number of shoot per explant (102). For elongation of shoots, MS basal medium gave a better response compared to ½ MS Medium. The average shoot elongation was about 3.3 cm and this gave an average of 7 leaflets per shoot. Elongated shoots were rooted and leaves growth using MS basal liquid medium and MS basal solid medium with or without 1 mg/l NAA (1-Naphthalene acetic acid). The best response for root induction and leaves growth was observed using MS basal liquid medium without NAA and this gave a frequency of 12 roots per shoot with an average length of 2.75 cm. The regenerated plantlets were acclimatized and hardened by transferring the test-tube plantlets into sterile water for 2 days. The plantlets were successfully established in soil containing compost and top soil (1:1) and the frequency of establishment was 90%. The clonal plantlets were verified using RAPD analysis. The results showed a very high frequency of true-to-type plantlets.